2007
DOI: 10.1016/j.envpol.2006.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Florida seagrass habitat evaluation: A comparative survey for chemical quality

Abstract: Some anthropogenic contaminants were prevalent in seagrass and their rooted sediments but the biological significance is unknown. AbstractContaminant concentrations were determined for media associated with 13 Florida seagrass beds. Concentrations of 10 trace metals were more commonly detected in surface water, sediment and two seagrass species than PAHs, pesticides and PCBs. Concentrations of copper and arsenic in surface water exceeded Florida aquatic life criteria more frequently than other trace elements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 40 publications
0
22
1
1
Order By: Relevance
“…Diuron concentrations, however, were as high as 25 g/L. Concentrations of 25 pesticides were below detection in 13 Florida seagrass beds [45].…”
Section: Surface Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Diuron concentrations, however, were as high as 25 g/L. Concentrations of 25 pesticides were below detection in 13 Florida seagrass beds [45].…”
Section: Surface Watermentioning
confidence: 99%
“…Concentrations (g/L) reported for other seagrass sites include those near Corpus Christi, Texas, USA, which were between 10.2 and 15.0 (zinc), 0.9 and 2.5 (copper), 9.0 and 13.9 (nickel), and 0.4 to 0.6 (cadmium) [44]. Lewis et al [45] reported that arsenic (36.3-70.7 g/L) and copper (13.9-61.1 g/L) were commonly detected over 13 Florida grass beds containing T. testudinum and Halodule wrightii but not cadmium, selenium, and silver. In the same study, 23 polyaromatic hydrocarbon (PAH) compounds and 18 polychlorinated biphenyl (PCB) congeners were below method detection limits (method detection limits range ϭ 4-19 g/L).…”
Section: Surface Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Human activities such as coastal land disturbance, motor boating and dredging increases pollutants (Burkholder et al 2007; Lewis et al 2007). One way to measure the degree of pollution is by using seagrass as a bioindicator for metal contamination (Ferrat et al 2003;Prange & Dennison 2000;Schlacher-Hoenlinger & Schlacher 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-nine percent of the estuarine areas of the U.S. Gulf of Mexico, which are essential nursery and spawning grounds for many finfish and sharks, assessed from 1997 through 2000, were considered impaired or threatened (USEPA 2004). Coastal wetlands and nearshore seagrass beds are critical nursery and spawning grounds for many finfish and sharks; however, Lewis et al (2007) estimated that 78 square kilometers (km 2 ) (30 miles 2 ) of wetlands were being lost annually and that 20-100 % of the seagrasses have been destroyed in some areas of the Gulf of Mexico. The deterioration and even total loss of these critical habitats may greatly reduce the carrying capacity of the Gulf of Mexico for many fish and shark species that depend on these areas as their critical habitat.…”
mentioning
confidence: 99%